2017
DOI: 10.1002/chem.201704440
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sustainable Zinc Anodes for a Rechargeable Hybrid Aqueous Battery

Abstract: The synthesis of novel zinc electrodes has been successfully implemented by using the electroplating method with the aid of inorganic additives in the electroplating solution. The selected inorganic additives are indium sulfate, tin oxide, and boric acid. From X-ray diffraction results, these synthesized zinc electrodes prefer (002) and/or (103) crystallographic orientations, representing basal morphology and high resistance to dendrite growth. The corrosion rates of these electroplated zinc samples decrease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 45 publications
5
96
0
Order By: Relevance
“…Furthermore, the SAED image revealed the well‐sustained crystalline structure with apparent diffraction spots of (200) and (220) and a good cubic structure after the long cycling process, which was also evidenced by the XRD patterns of FeHCF cathode before and after cycling as mentioned above in Figure S7 (Supporting Information). Besides, the electrochemically stable plating/stripping during the repeated charging/discharging processes of Zn electrode also plays a significant role in this ultralong‐term cycling, which was convincingly demonstrated by the voltage–time curve with long lifespan yet low polarization at both low and high current densities (1 and 10 mA cm −2 , corresponding to 60 and 6 min per cycle, respectively), and dendrite‐free surface (Figure S14, Supporting Information) . This ultralong lifespan of 10 000 cycles with a high capacity retention of 73% outperforms all of the Zn–PBA batteries reported before (Figure h), demonstrating the enormous potential of the high‐voltage‐induced activation strategy …”
mentioning
confidence: 64%
“…Furthermore, the SAED image revealed the well‐sustained crystalline structure with apparent diffraction spots of (200) and (220) and a good cubic structure after the long cycling process, which was also evidenced by the XRD patterns of FeHCF cathode before and after cycling as mentioned above in Figure S7 (Supporting Information). Besides, the electrochemically stable plating/stripping during the repeated charging/discharging processes of Zn electrode also plays a significant role in this ultralong‐term cycling, which was convincingly demonstrated by the voltage–time curve with long lifespan yet low polarization at both low and high current densities (1 and 10 mA cm −2 , corresponding to 60 and 6 min per cycle, respectively), and dendrite‐free surface (Figure S14, Supporting Information) . This ultralong lifespan of 10 000 cycles with a high capacity retention of 73% outperforms all of the Zn–PBA batteries reported before (Figure h), demonstrating the enormous potential of the high‐voltage‐induced activation strategy …”
mentioning
confidence: 64%
“…The achieved 98% coulombic efficiency for Zn‐Al‐LDH electrode is much higher than that for bare metallic Zn (≈85%). Chen and co‐workers prepared plating zinc electrode possessing less hydrogen gas evolution and dendrite formation by an optimized neutral electrolyte (0.6 m zinc sulfate and 0.1 m ammonium sulfate) containing selected inorganic additives (indium sulfate, tin oxide, and boric acid). The advantages can be ascribed to the special crystallography and surface texture of the plating zinc materials .…”
Section: Aqueous Batteries Using Multivalent Ions (Zn2+ Mg2+ Ca2+ mentioning
confidence: 99%
“…Chen and co‐workers prepared plating zinc electrode possessing less hydrogen gas evolution and dendrite formation by an optimized neutral electrolyte (0.6 m zinc sulfate and 0.1 m ammonium sulfate) containing selected inorganic additives (indium sulfate, tin oxide, and boric acid). The advantages can be ascribed to the special crystallography and surface texture of the plating zinc materials . Very recently, Fan and co‐workers reported the dendrite‐free zinc battery, in which a Zn nanoflakes array anode and an optimized quasi‐solid‐state electrolyte are explored.…”
Section: Aqueous Batteries Using Multivalent Ions (Zn2+ Mg2+ Ca2+ mentioning
confidence: 99%
“… 39 Various electrolyte additives including both organic and inorganic in electrodeposition for the Zn anode were proven to alter the preferred crystal orientation and the surface texture 40,41 . Typically, the adding of boric acid was found to transfer the preferred plane from (103) to (002) (Figure 2A) and showed a dense and orientated texture (Figure 2B) delivering better electrochemical chemical performance than the deposited the Zn anode with other selected additives or commercial Zn foil 42 . Artfully, Archer et al reported reversible epitaxial electrodeposition of a Zn anode using the low lattice mismatch material‐graphene to lock the crystallographic orientation of the deposited Zn 43 .…”
Section: Strategies Toward Dendrite Free the Zn Anodementioning
confidence: 99%
“…A, XRD results of electroplated Zn with 0, 50, 100, and 500 ppm of boric acid and commercialized Zn foil, B. SEM images of Zn deposits with 0 (no additive), 50, 100, and 500 ppm of boric acid in electroplating bath (magnification 1 k). Reproduced with permission from Reference 42. Copyright 2019 WILET‐VCH…”
Section: Strategies Toward Dendrite Free the Zn Anodementioning
confidence: 99%